Fiscal Asymmetric Decentralization Conundrum: Influence of County Cash Management on Household Effects in Kenya - Munyua, Cyrus; Muchina, Stephen; Ombaka, Beatrice (International Journal of Applied Business and International Management, 2020)
This study aims at determining the influence of county cash management on household effects in Kenya. This is a qualitative research that has utilized both primary and secondary data from county governments and the National Treasury respectively. The sample has been developed from the Kenya National Bureau of Statistics list of households in Kenya. The result indicates that effective cash management would enhance household welfare, leakages and lack of prioritization among others notwithstanding. The study concludes that there is need to enhance oversight of the treasury management across governments. The capacity of treasury managers should also be improved to secure fiscal discipline.